Perception Factors, Intentions and Attitudes with Market Community Participation to Prevent Occupational Diseases - Hariza Adnani; AA Subiyanto; Diffah Hanim; Endang Sutisna Sulaeman (Intelektual Pustaka Media Utama, 2018)
An Occupational Disease was a disease caused by work or work environment. One of the efficient and effective strategies for controlling Occupational Disease was the empowerment and participation of the community called Occupational Health Unit (Pos UKK) in the workplace. Based on the data of market health inspection in Pos UKK Imogiri market in March 2017, there were only 67 participants (19.17%) from 365 invited people.: The purpose of this research was to know the internal factors with the community participation in Pos UKK Imogiri market Bantul. This research was a quantitative analytic research with cross sectional design. The population was 365 people and the sample was 150 respondents. The sampling used purposive sampling technique. Kendall Tau test showed that there was a relation between perception and community participation (p value <0.05, r = 0.677); Intentions related to community participation (p value <0.05 r = 0.486); Attitudes related to community participation (p value <0.05 , r= 0.802). F test result showed that the variables of Perception, Intentions and Attitudes related simultaneously to community participation (F value = 387.41> F table = 2.67). The dominant independent variable was Attitudes with the highest Standard Beta Coefficient value was 0.776. Perceptions, Intentions and Attitudes related both partially and simultaneously to community participation; the independent variable that had dominant influence was Attitudes.